V. The hagiographic topic in I. S. Shmelev’s novel The Inexhaustible Chalice - Kochetkova O. L; Gaponova Yu. (Слово.ру: балтийский акцент, 2018)
In this article, we discuss the hagiographic topics in I. S. Shmelev’s novel The Inexhaustible Chalice, which are expressed through different components of the novel’s literary structure — ranging from the individual traits of the main character, Ilya Sharonov, to twists of the plot and the milestones of his biography. We maintain that in terms of the genre this novel resembles both the lives of the righteous and the lives of the venerable. The novel conforms to the canons of hagiographic texts because of the presence of a righteous character, whose image is built in accordance with the traditional paradigm of the positive qualities of a saint. Other reasons for such conformity include the biographical topic, namely, a stable set of events and facts, affecting the life and fate of the character, and such structural plot elements as the character’s dreams and visions, as well as signs and miracles, which testify to his initiation into sacred knowledge and visions. The topic of the ‘angelic image’, which is manifested in the character’s physical resemblance to an angel, also contributes to the conformity with the hagiographic canon.